Covid-19 Pandemic: Maximizing Future Vaccination Treatments Considering Aging and Frailty - Palermo, Sara (Frontiers in Medicine, 2020)
The COVID-19 pandemic is proving to be a multiplier of inequalities. Especially towards the elderly population. A voiceless scream that comes from geriatrics, nursing homes, hospices from all over Italy. They call it the silent massacre: from North to South, the bulletin of coronavirus positive - or already deceased - elderly people continues to grow exponentially without a chance to counter it. Population ageing and chronicity are a question that needs to be addressed. Frailty is the most challenging expression of population ageing, with major consequences for public health and clinical practice. It is a geriatric syndrome which consists in a state of higher vulnerability to stressors attributed to a lower homeostatic reserve due to an age-related multisystem physiological change. People over 60, and especially over 80, are particularly vulnerable to severe or fatal infection. Moreover, the age-related dysregulation of the immune system in the elderly results in poorer responses to vaccination. Physical frailty is an effective health indicator and it has previously shown to predict the response to the seasonal flu vaccine. These findings suggest that assessing frailty in the elderly may identify those who are less likely to respond to immunization and be at higher risk for COVID-19 and its complications. Moreover, cognitive frailty and reduced awareness of illness negatively impact on adherence to complex medication regimens among elderly patients. Considered the above, I suggest the importance to consider ageing in thinking about future Civud-19 vaccination and treatment, focusing on the possible impact of physical and cognitive frailty.